2011
DOI: 10.1097/ccm.0b013e31821bd79e
|View full text |Cite
|
Sign up to set email alerts
|

Does linezolid modulate lung innate immunity in a murine model of methicillin-resistant Staphylococcus aureus pneumonia?*

Abstract: Linezolid did not display an advantage over vancomycin in modulating pulmonary innate immune response in a murine model of methicillin-resistant S. aureus pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
14
1
Order By: Relevance
“…This is the first study to show that LZD did not have an effect on genome-wide host lung innate immunity at the mRNA level. This novel finding is consistent with the previous findings reported by Akinnusi et al (2011), who showed that LZD exhibits a minimal modulatory effect on protein levels of IL-6 and MCP-5 in a murine model of MRSA-pneumonia [12]. However, Garcia-Roca et al (2006) demonstrated that LZD significantly suppressed the synthesis of the cytokines (IL6, TNFα, IL-1ra and IL-1β) in human peripheral blood mononuclear cells [26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is the first study to show that LZD did not have an effect on genome-wide host lung innate immunity at the mRNA level. This novel finding is consistent with the previous findings reported by Akinnusi et al (2011), who showed that LZD exhibits a minimal modulatory effect on protein levels of IL-6 and MCP-5 in a murine model of MRSA-pneumonia [12]. However, Garcia-Roca et al (2006) demonstrated that LZD significantly suppressed the synthesis of the cytokines (IL6, TNFα, IL-1ra and IL-1β) in human peripheral blood mononuclear cells [26].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, exotoxin release leads to a corresponding increase in induction of tumor necrosis factor, which can be also suppressed with LZD [9-11]. Using a murine model of pneumonia, Akinnusi et al (2011) reported that LZD and VAN have comparable effects in modulating the expression of metalloproteinases (MMPs) in bronchoalveolar lavage fluid (BALF) and in regulating neutrophil activation [12]. They concluded that LZD exhibits a minimal modulatory effect on innate immunity in the animal model of MRSA pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…LZD (0.4 mg/mouse; 12 mg/kg of body weight) or vancomycin (VCM) (Shionogi & Co., Ltd., Osaka, Japan) (1 mg/mouse; 40 mg/kg) was subcutaneously (s.c.) admin-istered to mice immediately after intranasal administration of MRSA suspension (30 l/mouse; approximately 10 6 to 10 7 CFU/mouse). The administration doses of LZD and VCM were determined by reference to the previous reports (1,2,12,13,30,31). In some experiments, lower doses of LZD than described in the previous reports were selected to evaluate antiinflammatory effects not related to the bacterial killing effects.…”
Section: Datamentioning
confidence: 99%
“…While some murine studies have supported this hypothesis, others do not (1,2,14). The lack of considerable benefit with linezolid over vancomycin in mouse models of S. aureus infection has raised uncertainties about the potential benefits of linezolid in humans (6).…”
mentioning
confidence: 99%